Eu(III)-coordination polymer: inhibitory activity on cervical cancer via inducing ROS mediated apoptosis. (1st December 2020) - Hong, Dan; Zhao, Hong-Mei
Abstract: Under the hydrothermal reaction condition, we prepared a new 3D Eu(III)-based coordination polymer (CP) [Eu(H2 -DHBDC)0.5 (DHBDC)0.5 (H2 O)2 ] n ·H2 O (1, H4 -DHBDC = 2, 5-dihydroxy-1, 4-terephthalic acid). Furthermore, we assessed the inhibitory influence on cervical cancer cells of this compound. First, for testing the anti-viability of the compound against cervical cancer cells, the cell counting kit-8 (CCK-8) assay was carried out. Then, reactive oxygen species (ROS) detection kit was used to determine the ROS accumulation in the cervical cancer cells. Finally, after the Annexin V-FITC/PI apoptosis assay was finished, it was used for apoptotic cervical cancer cells after treated with compound. From the results of the software of pose scoring and molecular docking, we can see that the compound may bind to p91 by the functional side-chain of the ligand, which provided potential regulatory mechanisms for the compound.